Pemanfaatan Lingkungan Sebagai Laboratorium Alam Dalam Pembelajaran Siswa SMPN 17 Baubau - Dewi Asriani Ridzal; Haswan Haswan; Veni Rosnawati; Aulia Ahmad (Universitas Negeri Gorontalo, 2023)
Natural science is a subject that in the study requires a laboratory as a means of learning. The facts obtained are that there are still students who do not understand that the implementation of laboratory practicum can not only perform indoors (closed laboratory) but in an environment known as a natural laboratory. The method of community service activities carried out is socialization. Learning by utilizing the environment is very important to perform because the surrounding provides various things that students can study and can increase real student experience because it is very thick with everyday life. The evaluation result of understanding regarding the use of the environment as a natural laboratory showed that 83% (15 students) were in the excellent category, 11% (2 students) were in enough category and 6% (1 student) were in the poor category. These results indicate that most students have good knowledge about the advantage of the environment as a natural laboratory in learning.